2003
DOI: 10.1002/etc.5620220419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic amendments on the toxicity and bioavailability of cadmium and copper in spiked formulated sediments

Abstract: We evaluated the partitioning and toxicity of cadmium (Cd) and copper (Cu) spiked into formulated sediments containing two types of organic matter (OM), i.e., cellulose and humus. Amendments of cellulose up to 12.5% total organic carbon (TOC) did not affect partitioning of Cd or Cu between sediment and pore water and did not significantly affect the toxicity of spiked sediments in acute toxicity tests with the amphipod Hyalella azteca. In contrast, amendments of natural humus shifted the partitioning of hoth C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 48 publications
5
69
0
6
Order By: Relevance
“…These results reconfirmed OC as a major Cu-binding phase [3,4,11,43] and that the prediction of Cu bioavailability in sediments is significantly improved by normalizing particulate Cu concentrations to the concentrations of OC. The results were also consistent with the study by Costa et al [30], which reported 10-d LC50 values for the amphipod Gammarus locusta of 6.8, 57, and >200 mg Cu/kg for sediments with increasing amounts of silt and organic matter.…”
Section: Influence Of Sediment Properties On Cu Toxicitymentioning
confidence: 53%
See 2 more Smart Citations
“…These results reconfirmed OC as a major Cu-binding phase [3,4,11,43] and that the prediction of Cu bioavailability in sediments is significantly improved by normalizing particulate Cu concentrations to the concentrations of OC. The results were also consistent with the study by Costa et al [30], which reported 10-d LC50 values for the amphipod Gammarus locusta of 6.8, 57, and >200 mg Cu/kg for sediments with increasing amounts of silt and organic matter.…”
Section: Influence Of Sediment Properties On Cu Toxicitymentioning
confidence: 53%
“…30,2011and sulfide phases being oxidized at the sediment-water interface (SWI) [27]. Copper forms strong complexes with naturally occurring organic ligands, and the bioavailability and toxicity of dissolved Cu was expected to decrease with increasing DOC concentrations [4,11]. The DOC concentrations in the overlying waters were less than 1 mg/L in all tests.…”
Section: Influence Of Sediment Properties On Cu Partitioningmentioning
confidence: 97%
See 1 more Smart Citation
“…It is well recognised that partitioning between sediments and pore waters is greatly affected by sediment properties (Besser et al 2003, Simpson et al 2004. In estuarine/marine environments, cadmium exhibits a greater solubility than copper due to strong complexation by chloride, and for oxic surface sediments, Kd values are typically within an order of magnitude of 10 3 l kg -1 for cadmium and 10 4 to 10 5 l kg -1 for copper (Stumm & Morgan 1996).…”
Section: Effect Of Sediment Properties On Metal Exposure Pathwaysmentioning
confidence: 99%
“…Organic chelators, such as EDTA and dissolved organic matter, complex cupric ions to generally decrease toxicity [17]- [23], although increased toxicity is sometimes observed [24]. In seawater, organic matter content varies between 0.3 and 5 mg/L of carbon; about 90% of the dissolved copper is sorbed to this NOM [25].…”
Section: Introductionmentioning
confidence: 99%